Educação e ética: exercício da cidadania no processo de construção de uma sociedade justa - Marcolino, Maria Aparecida Custodio (2018)
This research is the result of reflections on ethical distortions that significantly influence the quality of education, preventing the free and full exercise of citizenship. It concerns that we are living in a critical period, especially in what refers to the realm of corruption in contemporary society. In this scenario, we highlight the occurrence of various forms of social injustice, present in different sectors and environments such as health, politics, the media, education and the family. We observe that coexistence is continuously permeated by technology, in a wide territory of expressions such as racism, homophobia and xenophobia that result in manifestations of intolerance and violence, which intensify socioeconomic inequalities and call for reflections, especially on the issue of ethics in education. The problematic described in the present context justifies the general objective of this research: to analyze the meaning of ethics in education, identifying its conception expressed in the pedagogical practices experienced in a school of Basic Education, enrolled in its Political Pedagogical Project and School Plan, and according to the vision of teachers and managers. The methodology adopted is characterized by a qualitative approach and a bibliographic study, with a view to delimiting the theoretical framework based on the production of relevant authors, among them Bergoglio, Comenius, Adussel, Freire, Gadotti, Saviani and Sacristán. The research also uses, as a methodological procedure, the documentary analysis and the field research developed, through interviews guided by semistructured scripts. The objective achieved, through the experiences and observations, was peculiar, and through the analyzed reports of teachers and managers, it is observed that the school curriculum goes beyond content, valuing the riches of all cultures, that ethics compose one of the pillars of education, constitutes together with the epistemological and pedagogical character in the ethical commitment in the practice that can order questions for possible later studies regarding the subject so relevant and current